2015
DOI: 10.1590/abd1806-4841.20153408
|View full text |Cite
|
Sign up to set email alerts
|

Dapsone in the treatment of pemphigus vulgaris: adverse effects and its importance as a corticosteroid sparing agent

Abstract: Pemphigus vulgaris is an autoimmune disease characterized by suprabasal blisters with acantholysis, which has a fatal course in a large number of untreated patients. Systemic corticosteroid therapy is considered first-line therapy. Adjuvant treatment with the goal of sparing corticosteroids include, among others, dapsone. This drug is not without side effects and its use requires clinical and laboratory control. We present a patient with PV initially managed with suboptimal dose of prednisone, evolving into dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
1
Order By: Relevance
“…A study revealed that this drug was the most common cause of acquired methemoglobinemia, which is caused by hydroxylamine, a dapsone metabolite. 16 Although sulfamethoxazole-trimethoprim is not a drug of treatment for pemphigus vulgaris, this drug was prescribed to our patient because he presented infection in different body sites. Sulfamethoxazoletrimethoprim was prescribed due to its ability to control superinfections, mainly by Staphylococcus aureus, and also due to the indirect immunomodulatory effect, regulating the secretion of IL-1 and TNF-α.…”
Section: Discussionmentioning
confidence: 93%
“…A study revealed that this drug was the most common cause of acquired methemoglobinemia, which is caused by hydroxylamine, a dapsone metabolite. 16 Although sulfamethoxazole-trimethoprim is not a drug of treatment for pemphigus vulgaris, this drug was prescribed to our patient because he presented infection in different body sites. Sulfamethoxazoletrimethoprim was prescribed due to its ability to control superinfections, mainly by Staphylococcus aureus, and also due to the indirect immunomodulatory effect, regulating the secretion of IL-1 and TNF-α.…”
Section: Discussionmentioning
confidence: 93%
“…There are studies showing that dopsone treatment may have serious adverse effects. [13] Pemphigus is a bullous, rare and chronic autoimmune disease. There are two major forms of pemphigus: vulgaris and foliaceus.…”
Section: Discussionmentioning
confidence: 99%
“…Até o presente momento, não há consenso no manejo terapêutico de pacientes portadores de pênfigo, devendo ser consideradas as particularidades de cada caso. No entanto, corticosteroides sistêmicos são considerados a primeira linha de tratamento para reduzir a produção de autoanticorpos 7 , sendo a prednisona a droga mais utilizada. imunobiológico de alto custo e com possíveis complicações ainda não totalmente elucidadas 24,25 .…”
Section: 22unclassified